2012
DOI: 10.1007/s00035-012-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Floral allocation at different altitudes in highly autogamous alpine Chaetanthera euphrasioides (Asteraceae) in the central Chilean Andes

Abstract: Artículo de publicación ISI.In the alpine life-zone, increasingly slower and unpredictable pollination at the higher altitudes predict an increase in floral investment in strongly outcrossing, pollenlimited biotically pollinated plant species, but not in autonomously self-pollinating species. Plant size, floral and above-ground vegetative biomass and individual capitulum biomass were studied in highly autogamous Chaetanthera euphrasioides (DC.) F. Meigen (Asteraceae) at 2,400 m a.s.l. and 3,300–3,400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Invasive species allocate higher reproductive biomass in stress conditions like temperature, light intensity, and nutrient absorption along the altitudinal gradient than vegetative parts to complete a life cycle (Wenk & Falster, 2015). Similarly, X. strumarium maintained reproductive output at higher elevations in mountain environments as an adaptive strategy as educated by Arroyo et al (2013). Consequently, enhancing repro-…”
Section: Discussionmentioning
confidence: 99%
“…Invasive species allocate higher reproductive biomass in stress conditions like temperature, light intensity, and nutrient absorption along the altitudinal gradient than vegetative parts to complete a life cycle (Wenk & Falster, 2015). Similarly, X. strumarium maintained reproductive output at higher elevations in mountain environments as an adaptive strategy as educated by Arroyo et al (2013). Consequently, enhancing repro-…”
Section: Discussionmentioning
confidence: 99%
“…In a highaltitude region, plants grow in a harsh habitat that restricted their effective utilization of resources; in this regard, the total available resource is less compared with that of plants in other regions (Fabbro and Körner, 2004;Hautier et al, 2009). In long-term evolution, the allocation of accumulated carbohydrates to reproduction is an adaptation strategy, leading to the partitioning of reproductive organs, that is, the availabil- ity and timely mobilization of adequate resources from the vegetative plant body to reproductive structures (Arroyo et al, 2013). Thus far, probably due to reproductive organs' comparatively minor biomass production and difficulty in being collected, studies on their decomposition have been limited particularly compared with those on leaf and other vegetative organs.…”
Section: Introductionmentioning
confidence: 99%
“…Invading species need more reproductive biomass than vegetative biomass to complete their life cycles when confronted with environmental stresses such as temperature, nutrients, and uptake light intensity along with an elevational gradient (Wenk and Falster, 2015). A similar adaption strategy was discovered by Arroyo et al (2013) in mountain habitats, where plants maintained reproductive output even at higher elevations (2013). We found that when elevation increases, S. marianum's reproductive ability takes priority over its vegetative ability.…”
Section: Discussionmentioning
confidence: 81%